2006
DOI: 10.1038/ncb1462
|View full text |Cite
|
Sign up to set email alerts
|

Yeast kinesin-8 depolymerizes microtubules in a length-dependent manner

Abstract: The microtubule cytoskeleton and the mitotic spindle are highly dynamic structures, yet their sizes are remarkably constant, thus indicating that the growth and shrinkage of their constituent microtubules are finely balanced. This balance is achieved, in part, through kinesin-8 proteins (such as Kip3p in budding yeast and KLP67A in Drosophila) that destabilize microtubules. Here, we directly demonstrate that Kip3p destabilizes microtubules by depolymerizing them--accounting for the effects of kinesin-8 perturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
609
5
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 428 publications
(663 citation statements)
references
References 29 publications
46
609
5
3
Order By: Relevance
“…We determined the speed by linear fits to the tracked x position. The speed was 40 5 2 nm/s (N ¼ 52, mean 5 SE unless noted otherwise), consistent with previous reports (24,28,29). With the trap turned on and no load applied in any direction (zero-force feedback), the speed was 39 5 2 nm/s (N ¼ 90, zero-force data point in Fig.…”
Section: Applying Sideward Loads With Optical Tweezerssupporting
confidence: 88%
See 2 more Smart Citations
“…We determined the speed by linear fits to the tracked x position. The speed was 40 5 2 nm/s (N ¼ 52, mean 5 SE unless noted otherwise), consistent with previous reports (24,28,29). With the trap turned on and no load applied in any direction (zero-force feedback), the speed was 39 5 2 nm/s (N ¼ 90, zero-force data point in Fig.…”
Section: Applying Sideward Loads With Optical Tweezerssupporting
confidence: 88%
“…Instead of transporting cargo, Kip3 depolymerizes microtubules and thereby regulates their dynamics and length (24)(25)(26). To do so, the motor needs to reach the microtubule end and thus, ideally, should have two features: 1) it should be highly processive-taking many steps without dissociating from the microtubule; and 2) it should be able to bypass obstacles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF18A operates at kinetochores 106 , whereas KIF18B is found on astralmicrotubules 107,108 . Some of the members of the kinesin-8 family are highly processive, and initial work on S. cerevisiae Kip3 indicated that it has depolymerase activity 49,109 . However a depolymerase activity for KIF18 from non-budding yeast is controversial (for review see 110 ).…”
Section: Kinetochore-mediated Pushing and Pullingmentioning
confidence: 99%
“…In fission yeast, the Dam1 complex is required only if kinesin-8 is absent, suggesting kinesin-8 performs a redundant function (20). Kinesin-8 is a plus-end directed motor that acts as a length-dependent depolymerase (21). Its ability to substitute for the Dam1 complex is especially interesting considering that, evolutionarily, the kinesin-8s are the next closely related clade to the kinesin-13s (see below) and may possess mechanistic similarities (21)(22)(23).…”
Section: The Dam1 Complex: Rings Around Microtubulesmentioning
confidence: 99%